Hypo-fractionated stereotactic radiotherapy alone using volumetric modulated arc therapy for patients with single, large brain metastases unsuitable for surgical resection. Issue 1 (December 2016) - Navarria, Pierina; Pessina, Federico; Cozzi, Luca; Ascolese, Anna; De Rose, Fiorenza; Fogliata, Antonella; Franzese, Ciro; Franceschini, Davide; Tozzi, Angelo; D'Agostino, Giuseppe; Comito, Tiziana; Iftode, Cristina; et al.
Abstract Background Hypo-fractionated stereotactic radiotherapy (HSRT) is emerging as a valid treatment option for patients with single, large brain metastases (BMs). We analyzed a set of our patients treated with HSRT. The aim of this study was to evaluate local control (LC), brain distant progression (BDP), toxicity and overall survival (OS). Methods From July 2011 to May 2015, 102 patients underwent HSRT consisting of 27Gy/3fractions for lesions 2.1–3 cm and 32Gy/4 fractions for lesions 3.1–5 cm. Local progression was defined as increase of the enhancing abnormality on MRI, and distant progression as new brain metastases outside the irradiated volume. Toxicity in terms of radio-necrosis was assessed using contrast enhanced T1MRI, T2 weighted-MRI and perfusion- MRI. Result The median maximum diameter of BM was 2.9 cm (range 2.1–5 cm), the median gross target volume (GTV) was 16.3 cm3 and the median planning target volume (PTV) was 33.7 cm3 The median, 1, 2-year local control rate was 30 months, 96, 96 %; the median, 1–2-year rate of BDP was 24 months, 12, 24 %; the median, 1, 2-year OS was 14 months, 69, 33 %. KPS and controlled extracranial disease were associated with significant survival benefit (p <0.01). Brain radio-necrosis occurred in six patients (5.8 %). Conclusion In patients with single, large BMs unsuitable for surgical resection, HSRT is a safe and feasible treatment, with good brain local control and limited toxicity.